Evaluation of different artificial intelligence applications in responding to regenerative endodontic procedures - Ece Ekmekci; Parla Meva Durmazpinar (BMC Oral Health)
Abstract Introduction The integration of artificial intelligence (AI) technologies in healthcare is revolutionizing the workflows of healthcare professionals, enabling faster and more accurate patient treatment. This study aims to evaluate the accuracy of responses provided by different AI chatbots to questions that dentists might ask regarding regenerative endodontic treatment (RET), a procedure that shows promising biological healing potential. Methods A total of 23 questions related to RET procedures were developed based on the American Association of Endodontists (AAE) 2022 guidelines. These questions were presented to three platforms: Google Bard (Gemini), ChatGPT-4o, and ChatGPT-4 with a PDF plugin. The questions were asked three times a day over the course of 10 days by two different researchers. The responses obtained were categorized as correct, incorrect, or insufficient according to the guidelines, and the results were statistically analyzed. Results A total of 1,380 responses were collected from the three platforms. Statistical analysis revealed significant relationships between the responses given by the platforms during morning, noon, and evening sessions (p < 0.05). ChatGPT-4 with the PDF plugin had the highest correct response rate (98.1%), while Gemini depicted the lowest (48%). Conclusions While ChatGPT-4o and Gemini offer promising results for regenerative endodontic clinical applications, they do not provide sufficient guidance. However, ChatGPT-4 with the PDF plugin could be a valuable tool for clinicians due to its high accuracy rate. Further research is needed to develop AI programs specifically designed for clinicians in the field of endodontics.